Treatment Facility Volume and Survival in Patients with Metastatic Renal Cell Carcinoma: A Registry-Based Analysis - Joshi, Shreyas S. (Eur Urol, 2018)
BACKGROUND: Higher treatment facility (TF) volume has been linked with improved oncologic treatment outcomes. OBJECTIVE: To determine the association between TF volume and OS in patients with metastatic RCC (mRCC). DESIGN, SETTING, AND PARTICIPANTS: The National Cancer Data Base (NCDB) was queried for all patients with mRCC with survival data available (2004 to 2013, cohort A). We defined high volume TFs as those in the top 20(th) percentile of mean number of mRCC patients treated per year, and also examined the association with continuous volume. Increasingly narrow inclusion criteria were used to confirm the cohort A association: Cohort B = mRCC patients with active treatment; cohort C = mRCC patients with systemic therapy; cohort D = mRCC patients with systemic therapy at the reporting institution; cohort E = mRCC patients with systemic therapy at the reporting institution with known liver and lung metastatic status. Survival analyses were also performed on sub-cohorts of mRCC who never underwent a nephrectomy (C1, D1, and E1). OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: The effect of volume on OS was determined using unadjusted Kaplan-Meier curves and Cox regression models (MVA) after adjustment for multiple clinicopathologic factors. RESULTS AND LIMITATIONS: There were 41,836 mRCC patients treated at 1,222 TFs. The median age was 65. 66% were men and 79% had clear cell mRCC. Median TF volume was 2.2 patients/year, (range 0.1–44.3). High volume TFs (≥4.8pts/year) treated 54% of all mRCC patients. The unadjusted median OS of all mRCC patients treated at high vs. low volume TFs was 9.5 vs. 6.5 months (P<0.0001). This difference was maintained in all cohorts: Cohort B=14.2 vs. 11.3, cohort C=12.6 vs. 10.1, cohort D=12.7 vs. 9.2, and cohort E=14.0 vs. 10.6 months (P < 0.0001 for all). MVA confirmed that facility volume was associated with OS after adjustment; cohort A: HR=0.85, [95% CI 0.82–0.88], P < 0.001. These results were consistent regardless of the cohort examined, even after exclusion of all nephrectomy patients. For all TFs treating ≥ 5 pts/yr, OS improved as TF volume increased (20 pts/yr: HR=0.75). Limitations include the retrospective nature of NCDB analysis and the lack of information on treatment regimens used at specific facilities, which may explain mechanisms of effects. CONCLUSIONS: Patients with mRCC treated at higher volume facilities had a longer survival compared with those treated at lower volume facilities. PATIENT SUMMARY: In this report we analyzed a large cancer database and found that patients with metastatic kidney cancer survived longer if they were managed at facilities that treated a higher volume of such patients. This information can be used as an aide to help find the best treatment environment for patients with metastatic kidney cancer.